OC-114 Effect of the low fodmap diet and oligofructose supplement on colonic volume, transit and fermentation: a double-blind randomised controlled trial using magnetic resonance imaging in healthy volunteers. (22nd June 2015) - Major, G; Krishnasamy, S; Mulvenna, C; Pritchard, S; Hoad, C; Marciani, L; Lomer, M; Gowland, P; Spiller, R
Abstract : Introduction: Fermentable oligo-, di-, mono-saccharides and polyols (FODMAPs) have been shown to cause pain, bloating and flatulence in irritable bowel syndrome (IBS) which can be reduced by a low FODMAP diet. Pain and bloating could be caused by visceral distension. We have previously shown that giving a typical FODMAP, oligofructose (OF), 5 gm b.d. for one week increased fasted colonic volume (CV) by 18% when measured with magnetic resonance imaging (MRI). Our aim was to determine whether a) a low FODMAP diet reduces CV b) whether this effect could be abolished by OF but not a control, maltodextrin (MD). Method: Design: A double-blind, parallel group, randomised controlled trial. 37 healthy subjects completed the study, 19 receiving OF and 18 MD. Procedures: fasting MRI and measurement of breath hydrogen (H2 ) and methane (CH4 ) at baseline and after one week of intervention. Food diaries were kept for one week before each MRI. 24 h before MRI subjects swallowed bespoke markers previously validated as a measure of GI transit. Interventions: All subjects followed the low FODMAP diet after advice from a registered dietitian. They were randomised (1:1) to supplement their diet with either MD or OF, 7 g twice daily. A standard food package (normal or low FODMAP) was provided for the 24 h preceding MRI. The study was powered to detect a 15% increase in CV on OF compared to MD. Results: All results expressed as mean (95% CI). All participants complied with the diet and supplements. One subject (MD) was excluded from MRI analysis for corrupted images. Baseline CV was 673 mL (617–728). CV increased on the low FODMAP diet in both groups: OF 19.6% (6.5–32.7) and MD 15.5% (2.5–28.4). The difference between groups was not significant. Fasting breath H2 rose significantly more on OF, by 16 ppm (–2–35) compared to baseline, than on MD which showed a fall of 11 ppm (3–18), p < 0.01. Transit and CH4 did not change with diet or show any difference between groups. Conclusion: The fall in breath H2 on low FODMAP diet with MD, an effect which was reversed by OF, confirms previous studies. 1, 2 CV increased on the low FODMAP diet, possibly because food substitutes for FODMAPs (e.g. tapioca, potato) contain substrate which can be utilised by colonic bacteria. Contrary to expectations a low FODMAP diet supplemented with MD did not cause a fall in colonic distension. The clinical benefit may be due to another mechanism, possibly related to changing microbiota. Disclosure of interest: G. Major: None Declared, S. Krishnasamy: None Declared, C. Mulvenna: None Declared, S. Pritchard: None Declared, C. Hoad: None Declared, L. Marciani: None Declared, M. Lomer: None Declared, P. Gowland: None Declared, R. Spiller Grant/ Research Support from: Lesaffre, Ironwood, Norgine, Falk Pharma, Consultant for: Almirall, Astellas, Yuhan, Danone. References: Ong, et al . 2010 Cani, et al . 2009